Organic field-effect transistors using single crystals - Tatsuo Hasegawa and Jun Takeya (Science and Technology of Advanced Materials, 2009)
Organic field-effect transistors using small-molecule organic single crystals are developed to investigate fundamental aspects of organic thin-film transistors that have been widely studied for possible future markets for 'plastic electronics'. In reviewing the physics and chemistry of single-crystal organic field-effect transistors (SC-OFETs), the nature of intrinsic charge dynamics is elucidated for the carriers induced at the single crystal surfaces of molecular semiconductors. Materials for SC-OFETs are first reviewed with descriptions of the fabrication methods and the field-effect characteristics. In particular, a benchmark carrier mobility of 20–40 cm2 Vs−1, achieved with thin platelets of rubrene single crystals, demonstrates the significance of the SC-OFETs and clarifies material limitations for organic devices. In the latter part of this review, we discuss the physics of microscopic charge transport by using SC-OFETs at metal/semiconductor contacts and along semiconductor/insulator interfaces. Most importantly, Hall effect and electron spin resonance (ESR) measurements reveal that interface charge transport in molecular semiconductors is properly described in terms of band transport and localization by charge traps.